Does financial literacy matter for firms? An empirical investigation on Sri Lankan SMEs - Geesara Kasthuri Arachchi; Ishan Perera; Chathurya Gamage; Shehara Wijesinghe; Krishantha Wisenthige; Nirmani Dayapathirana (PLoS ONE, 2026)
Small and Medium Enterprises (SMEs) are vital to economic growth and job creation, especially in developing countries. However, their potential is not fully utilized due to challenges related to limited financial inclusion, poor resource management, and underdeveloped capital markets. Though financial literacy is well-researched in personal finance, its role as a knowledge resource at the firm level and its impact on firm performance remain underexplored. This study investigates the influence of owner-managers’ financial literacy on firm performance, focusing on the mediating roles of FinTech adoption and access to finance. By taking a sample of 264 SME owner-managers in the Western Province of Sri Lanka, this study found that financial literacy significantly enhances firm performance ( β = 0.241, p < .01). The findings indicate that financial literacy supports sound financial decision-making and risk mitigation and is positively associated with both FinTech adoption ( β = 0.542, p < .001) and access to finance ( β = 0.533, p < .001). These results underscore the necessity of enhancing financial literacy and promoting FinTech adoption to fully realize the potential of SMEs within developing economies. The study contributes a concise yet impactful framework for enhancing the performance of SMEs through the strategic application of financial literacy. Based on the study’s findings, it is recommended that enterprise owners and managers prioritize achieving an adequate level of financial literacy. Furthermore, governmental institutions should revise their financial literacy programs, reconsidering their design and implementation strategies to effectively engage key personnel within enterprises. Current programs appear underutilized due to deficiencies in depth and practical applicability of the knowledge given in them.